Outcomes of Hindfoot and Ankle Arthrodesis in Patients with Charcot Neuroarthropathy - Vladimir A. Vinogradov; Stanislav A. Osnach; Victor G. Protsko; Vladimir N. Obolenskiy; Sargon K. Tamoev; Vasiliy V. Kuznetsov; Nikolay V. Zagorodniy; Levon G. Makinyan (Travmatologiâ i Ortopediâ Rossii)
Background. Involvement of the hindfoot and ankle in diabetic Charcot neuroarthropathy is often associated with subtotal or total defects of the talus, leading to unstable multiplanar deformities and a significant loss of weight-bearing capacity in the affected limb. Numerous arthrodesis techniques and fixation methods have been developed; however, in most cases, the final choice of surgical treatment depends on the surgeon’s preference.